Experiments with internal targets at the VEPP-3 electron storage ring; Physics of Atomic Nuclei; Vol. 73, № 8 - Nikolenko D. M.; Arenhövel H.; Arrington J.; Barkov L. M.; Belostotski S. L.; de Vries H.; Gilman R.; Gramolin A. V.; Dmitriev V. F.; Zevakov S. A.; Karnakov I. V.; Lazarenko B. A.; et al. (2010, 2010)
An overview of the recently completed, current, and planned experiments with internal targets at the VEPP-3 electron-positron storage ring in Novosibirsk is given. The results of the experiment to separately measure the deuteron form factors in elastic ed scattering in the range of momentum transfer Q 2 = 8−15 fm−2 are provided. The results of measuring the tensor analyzing power components of the tensor-polarized deuteron photodisintegration reaction in the range of γ-quantum energies E γ = 25−600 MeV are presented. The tensor analyzing powers of the coherent photoproduction of a neutral pion on a tensor-polarized deuteron have been measured for the first time. The almost-real photon tagging system being created is discussed. The status of the experiment under way to determine the contribution of two-photon exchange to the elastic ep scattering cross section is described